Perencanaan Jembatan Rangka Baja Pelengkung Sungai Liong - Febry Suhendra; Faisal Ananda; Alamsyah Alamsyah (Jurnal Teknik Sipil, 2018)
Bengkalis government do project to build Liong river bridge with construction type is concrete arch bridge. But at relatively new service time, there was a big deflection in one of bridge segments. In this research will be design the bridge with steel arch bridge type. Bridge design using RSNI T-02-2005 about bridge load standard. For steel frame design refers to RSNI T-03-2005, and concrete structure design refers to RSNI T-12-2004. In piles calculation, using the Schmertmann method. The results of top structure design is top chord using WF.305.305.22.35, bottom chord WF. 305.305.39.63, diagonal chord WF.305.305.22.35, vertical hanger WF 203.203.10.17, wind bracing WF.203.203.8.12, truss bracing WF.203.203.8.12, girder using WF.400.200.8.13, cross girder WF.500.200.10.16, and the main girder using WF.500.200.10.16 profile. The results of bottom structure design is abutment width of 9,3 m and abutment length of 11 m. Using concrete piles with diameter of 50 cm, length 20 m and 28 point of stake. The largest deflection of bridge is 118,72 mm. This deflection is still safe because the value smaller than tolerance deflection L/240, which is 458,33 mm. The most compatible construction method for liong II river bridge is temporary coloumn method.